Analysis of Cesarean Section using Robsons classification at Teaching Hospital of Eastern Nepal - Yadav, Siddhartha Kumar; Yadav, Indra; Pradhan, Tarun; Deo, Amit; Dhamala, Jibanath; Regmi, Upendra Krishna; Yadav, Mukesh; Jyoti, Sabita (Journal of Nepalgunj Medical College, 2023)
Introduction: Cesarean section is an operative procedure for delivery of fetus and placenta by making an incision over abdomen and uterus after period of viability.Aims: The aim of study is to analyze rate of cesarean section and perform an analysis based on Robsons ten group classification.Methods: A cross sectional study was conducted at Department of Obstetrics and Gynecology of a teaching hospital of eastern Nepal, over a period of one year from October 2022 to September 2023. All details regarding demography, obstetric history, medical history, labor status, indication of cesarean section, etc. were collected. Then all pregnant ladies were assigned to one of Robsons ten group classification systems and recorded into labor confinement book. The statistical analysis was performed using Statistical Package for Social Sciences version 21. Descriptive statistical tools were used to express the results. All tests were done with a significance level of 5% (p-value 37 weeks of gestation. Majority 789(43.10%) of cases had lower segment cesarean section because of previous cesarean delivery. According to Robsons classification system, Group 5 has highest cesarean section rate 725 (39.60%) followed by Group 2(A+B), 334(18.21%).Conclusion: Implementing Robsons Ten Group Classification System at our setting has helped us to identify major contributor of overall cesarean section rate. Group 5 was at top followed by group 2. Thus with adequate trial of labor after cesarean, proper labor monitoring and judicious use of induction protocol can significantly reduce rate of cesarean section.